Nigeria And Her Immediate Neighbours In The Post Colonial Era: A Critical Analysis - Ogbu, Barr. Solomon; Olakunle, Osunyikanmi Pius (Advances in Social Sciences Research Journal, 2019)
The paper provides a lucid analysis of Nigeria’s relationship with her immediate neighbours with a view to understanding the nature of her foreign policy towards the neighbouring countries. Nigeria has land borders with the Republics of Niger, Chad, Benin, and Cameroun, and also has maritime borders with the Republics of Benin, Chad, Cameroun, Equatorial Guinea, and Sao Tome and Principe. It is clear from the available literature that Nigeria has good diplomatic relations with her immediate neighbours, albeit occasional border disputes which are often resolved amicably. It is recommended that as the most populous, most economically powerful, and most militarily powerful nation among the immediate neighbours, it is advisable for Nigeria to maintain good relations with her neighbours for the sake of her national interest.